Transition of a Child with Autism Spectrum Disorder (ASD) from Special School to Inclusive School - Bhattacharya, Ankita; P, Gowramma I (JOURNAL OF INDIAN EDUCATION, 2024)
Autism Spectrum Disorder (ASD) is a developmental neural condition that typically becomes apparent in early childhood and continues throughout a person’s lifetime. Children with ASD encounter significant challenges in the development of their social skills, making their inclusion in mainstream schools a complex task. To address this issue, a case study was carried out on a 10 year old student with ASD who is currently attending a special school in Kolkata. The primary objective of this study is to pinpoint the gaps in the child’s learning in six distinct facets of social skills, which include social relationships and reciprocity, emotional responsiveness, speech-language and communication, behavioural patterns, sensory aspects and cognitive components. To achieve this, the INCEL diagnostic tool and a custom-designed interview schedule were employed. Subsequently, a transition plan tailored to the specific needs of the student was created to facilitat